A nonsmooth composite control design framework for nonlinear systems with mismatched disturbances : algorithms and experimental tests - Zhang, Chuanlin (2020)
In this paper, a nonsmooth composite control design methodology is investigated to tackle the exact tracking control problem for a general class of nonlinear systems with mismatched disturbances. By first introducing a saturated homogeneous disturbance observer to realize a finite-time performance recovery, a simple composite controller is then made feasible by virtue of the nonrecursive synthesis approach. A new feature is that under a less ambitious control objective, namely, semiglobal stability, various nonlinearity growth constraints for nonsmooth design approaches are essentially relaxed. Rigourous proof is provided to demonstrate the theoretical justifications. In order to illustrate the practical nature of the proposed design framework, a practical control application to series elastic actuator is presented. Experimental comparison results with the PID and finite-time controllers show significant performance improvements.